An elite athlete's storying of injuries and non-qualification for an Olympic Games: a socio-narratological case study. Issue 5 (20th October 2019) - Barker-Ruchti, Natalie; Schubring, Astrid; Post, Anna; Pettersson, Stefan
ABSTRACT: In this article, we present and examine the case of one elite athlete – 28-year old Mark (pseudonym), who during a 10-month lead-up to the 2016 Rio OG qualification deadline, aimed to achieve his NGB/NOC's qualification standards, but sustained several injuries and was forced to give up his qualification attempt. Adopting a socio-narratological framework, we aim to understand how Mark storied the qualification period; how socio-cultural, organisational, and biographical contexts complicated his qualification and how he handled these complications; and how he made sense of not qualifying. Based on data produced through a longitudinal prospective study that included a background questionnaire, three semi-structured interviews, a weekly web survey, a training observation, and a compilation of competition results, our socio-narratological interpretations evidence that Mark aligned his athletic life to the 'sport performance investment narrative', but that this narrative provided limited resources to story poor competitive results and injuries. Instead, as Mark faced unexpected disruptions, he adopted a number of restitution strategies (e.g. alternative training/competition plans; positive thinking; rehabilitation) to re-align to the performance narrative. In so doing, Mark compromised injury recovery to worsen his performance and further injure his body, which eventually stopped his qualification process. After a directionless period and personal suffering, Mark again intended to follow the performance investment narrative. We propose that coaches, support staff and sport organisations recognise the pressurised nature of a qualification phase and provide support strategies to moderate instability and possible non-qualification.